Topical Vancomycin in Cardiac surgery to reduce Sternal wound Infections: A Randomized Controlled trial at a Tertiary Cardiac Care facility - Farrah Pervaiz; Imtiaz Ahmed Chaudhry; Rehana Javaid; Hafsa Khalil; Javeria Kamran; Fatima Khattak; Rahmeen Pervaiz Khan; Afsheen Iqbal (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Objective: To determine the effectiveness of topical vancomycin in reducing the incidence of sternal wound infections (SWI) in patients undergoing coronary artery bypass graft (CABG) surgery. Study design: Randomized Controlled Trial (RCT). Material and methods: This double blinded randomized clinical trial was carried out on 276 patients scheduled for elective CABG surgery. Patients were divided into two equal groups. In patients of group A (n=138) topical vancomycin solution was used in the sternal wound, and patients in group B (n=138) topical normal saline before sternal wound closure in coronary artery bypass graft surgery. The incidence of sternal wound infection was followed over an 18 months period. Major risk factors like diabetes mellitus (DM), smoking, and prolonged operation time i,e cardiopulmonary bypass time (CPB time) and cross clamp time were also evaluated.  Results: There was no significant difference between the two groups in demographics (age, gender, body mass index (BMI) and co-morbids like hypertension and smoking. Vancomycin group had more diabetic patients than the normal saline group. The cost effectiveness of the two topical agents was also compared (p <0.001).  Conclusion: Topical vancomycin and normal saline had no significant influence on the incidence of SWI rate in 276 consecutive cardiac surgery patients.